2006
DOI: 10.1523/jneurosci.5401-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reward and Behavioral Context on Neural Activity in the Primate Inferior Colliculus

Abstract: Neural activity in the inferior colliculus (IC) likely plays an integral role in the processing of various auditory parameters, such as sound location and frequency. However, little is known about the extent to which IC neural activity may be influenced by the context in which sounds are presented. In this study, we examined neural activity of IC neurons in the rhesus monkey during an auditory task in which a sound served as a localization target for a saccade. Correct performance was rewarded, and the magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 52 publications
5
46
0
1
Order By: Relevance
“…They can be distinguished from ongoing slow fluctuations of neuronal activity (Steriade et al, 1993;He, 2003;Filippov et al, 2008;Gao et al, 2009) by being related to or evoked by specific external or internal events. Event-related slow firing changes in auditory cortex (Gottlieb et al, 1989;Quirk et al, 1997;Armony et al, 1998;Shinba et al, 1995;Selezneva et al, 2006) bear similarities with slowly changing activities that have previously been observed in subcortical stages of the auditory system, including inferior colliculus (Metzger et al, 2006) and non-primary thalamic nuclei (Komura et al, 2001(Komura et al, , 2005. Similar event-related slow firing changes (also termed built-up, ramping, or late responses) have been observed in other sensory systems, including early visual cortex (Rowland et al, 1985;Shuler and Bear, 2006), and in various non-sensory brain structures such as the basal ganglia (e. g., Schultz and Romo, 1992;, midbrain (e. g., Hernandez et al, 2006), prefrontral cortex (Niki andWatanabe, 1979;Morrison and Salzman, 2009) and motor structures (e. g., Mita et al, 2009) where they have been implicated with reinforcement, working memory, and preparatory set.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…They can be distinguished from ongoing slow fluctuations of neuronal activity (Steriade et al, 1993;He, 2003;Filippov et al, 2008;Gao et al, 2009) by being related to or evoked by specific external or internal events. Event-related slow firing changes in auditory cortex (Gottlieb et al, 1989;Quirk et al, 1997;Armony et al, 1998;Shinba et al, 1995;Selezneva et al, 2006) bear similarities with slowly changing activities that have previously been observed in subcortical stages of the auditory system, including inferior colliculus (Metzger et al, 2006) and non-primary thalamic nuclei (Komura et al, 2001(Komura et al, , 2005. Similar event-related slow firing changes (also termed built-up, ramping, or late responses) have been observed in other sensory systems, including early visual cortex (Rowland et al, 1985;Shuler and Bear, 2006), and in various non-sensory brain structures such as the basal ganglia (e. g., Schultz and Romo, 1992;, midbrain (e. g., Hernandez et al, 2006), prefrontral cortex (Niki andWatanabe, 1979;Morrison and Salzman, 2009) and motor structures (e. g., Mita et al, 2009) where they have been implicated with reinforcement, working memory, and preparatory set.…”
Section: Introductionsupporting
confidence: 64%
“…A few studies show that slow changes of firing with similar properties are also present in subcortical stages of the auditory system (Komura et al, 2001(Komura et al, , 2005Metzger et al, 2006;Fig. 5).…”
Section: Slow Firing Changes At Subcortical Stages Of the Auditory Symentioning
confidence: 99%
See 1 more Smart Citation
“…Despite occupying a pivotal position in the ascending auditory system, IC neurons are modulated by more than just acoustic stimuli. Several nonauditory factors such as visual stimuli, tactile stimuli, the position of the eyes, and impending reward also have a role in shaping neural activity (Aitkin et al 1981;Bergan and Knudsen 2009;Groh et al 2001;Gutfreund et al 2002;Mascetti and Strozzi 1988;Metzger et al 2006;Porter et al 2006Porter et al , 2007Zwiers et al 2004).…”
mentioning
confidence: 99%
“…The state of the animal (anesthetic, alertness) is one such factor (Ryan and Miller, 1977;Populin, 2005). Moreover, changes in eye position can weakly modulate IC activity (Groh et al, 2001;Zwiers et al, 2004), whereas Metzger et al (2006) observed relatively late response modulations related to task constraints. The origin of these modulations is unknown.…”
mentioning
confidence: 99%